TRADE LIBERALIZATION, STRUCTURAL CHANGE AND PRODUCTIVITY GROWTH: EVIDENCE FROM MONGOLIA - Bolor Khurelchuluun; Siqintana Bao (International Journal of Innovative Technologies in Social Science, 2024)
We analyze how Mongolia’s trade openness affects labor market structural changes and its contribution to manufacturing productivity growth. Our findings indicate that reducing import tariffs on intermediate goods resulted in a 1.70% shift of labor from state-owned enterprises (SOEs) to non-SOEs from 2001 to 2015, accounting for 2.96% of intra-industry labor flow. Intermediate import tariff reduction decreased costs for non-SOEs and alleviated financing constraints. Additionally, the shift in employment ownership due to trade openness improved resource allocation efficiency, explaining 3.51% of production efficiency growth from inter-enterprise factor allocation and 0.81%-1.12% of overall manufacturing productivity growth. This highlights its role as a key channel for enhancing productivity through trade openness.